L’île de Bilāq dans le Kitāb Nuzhat al-Muštāq d’al-Idrīsī (XIIe siècle). Généalogie d’une confusion - Robin Seignobos (Afriques)
The 12th-century description of Bilāq Island by al-Idrisi contrasts with his predecessors’ accounts and only partly fits the small island of Philae with which Bilāq was usually identified. Bilāq, normally placed a little above the first cataract, became, for al-Idrīsī, a big island located much farther upstream in the land of Nubia, at a place where a river coming from Ethiopia flowed into the Nile. Modern commentators agree that this description probably came out of a confusion with the Nile-Atbara area but are unable to explain the reasons for this. This article inquires into al-Idrisi’s description, into both the sources and methods used by this geographer. It intends to shed light on the origins of this confusion, which ultimately has to do with the difficulty that al-Idrīsī had adapting heterogeneous sources of information (including interviews with travelers) to his Ptolemaic conception. The island of Bilāq thus came to be mixed up with lingering recollections of the island of Meroe, a major figure in the Ptolemaic geography of the upper Nile Valley.